2021
DOI: 10.3390/ijms22073618
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analyses of Myometrium from Fibroid Patients Reveals Phenotypic Differences Compared to Non-Diseased Myometrium

Abstract: Uterine fibroid tissues are often compared to their matched myometrium in an effort to understand their pathophysiology, but it is not clear whether the myometria of uterine fibroid patients represent truly non-disease control tissues. We analyzed the transcriptomes of myometrial samples from non-fibroid patients (M) and compared them with fibroid (F) and matched myometrial (MF) samples to determine whether there is a phenotypic difference between fibroid and non-fibroid myometria. Multidimensional scaling plo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…Molecular studies also reveal that NPTX1 functions by regulating both Nodal ligands and bone morphogenetic proteins (BMP) signaling via binding to TDGF1, which regulates pluripotency and neural differentiation [37]. Both Nodal ligands and BMP are also members of the TGF-β family of ligands [38], which is in accordance with previous findings where TGF-β was considered a key player gene in UL [39] and further extends previously identified pathways to synaptic signaling. Furthermore, NPTX1 was also identified as a novel epigenetic regulator that was associated with prognosis in lung cancer [40].…”
Section: Discussionsupporting
confidence: 88%
“…Molecular studies also reveal that NPTX1 functions by regulating both Nodal ligands and bone morphogenetic proteins (BMP) signaling via binding to TDGF1, which regulates pluripotency and neural differentiation [37]. Both Nodal ligands and BMP are also members of the TGF-β family of ligands [38], which is in accordance with previous findings where TGF-β was considered a key player gene in UL [39] and further extends previously identified pathways to synaptic signaling. Furthermore, NPTX1 was also identified as a novel epigenetic regulator that was associated with prognosis in lung cancer [40].…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, due to the paracrine and mechanical effect of uterine fibroids, the manner of collecting the myometrium is a significant factor. Notably, the biology of myometrium from the uterus with fibroids or without fibroids differs ( 393 , 394 ). For these reasons and more, uterine fibroid studies need to be carefully designed and should take these factors into consideration.…”
Section: Key Pathways Contributing To Uterine Fibroids Formationmentioning
confidence: 99%
“…Omics studies also demonstrated that uterine fibroids contain disrupted epigenome linked with genetic stability ( 135 , 412 ). Notably, the myometrium of uterine fibroids patients has a distinct transcriptomic pattern compared with non-diseased myometrium ( 394 ), and cells from diseased myometrium responded differently to progesterone ( 413 ). These studies suggest that adjacent myometrium from the uterus with uterine fibroids should not be considered as normal tissue.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Von Willebrand Factor (VWF) and Brain Derived Neurotrophic Factor (BDNF) were induced in Black MyoF samples compared to White MyoF samples but not in the Black F samples compared to White F samples. Cyclin D1 (CCND1), which we have previously reported upregulated in F compared to MyoF (27), was not significantly induced in MyoF from Black women compared to MyoF from White women. Gene Set Enrichment Analyses (GSEA) (Fig 2C and D) was performed with Hallmark gene sets (34,35) to identify dysregulated pathways that could be important for the racial disparity We performed a clustering analysis of a leiomyoma gene set (39) with the addition of BDNF for MyoF and F samples in both race groups.…”
Section: Resultsmentioning
confidence: 66%
“…To minimize sample variability, only tissue samples from patients with MED12mt fibroids, which are the most common genetic subtype of uterine fibroids (26) S2) compared with the F samples (Fig 2A,198 total DEGs, Table S3). Three different genes that we thought could be differentially expressed in the tissues from Black and White women based on our previous studies (27,28) or that are candidate genes gleaned from the literature that could be important for stress-related fibrosis (29)(30)(31)(32)(33) are highlighted. Von Willebrand Factor (VWF) and Brain Derived Neurotrophic Factor (BDNF) were induced in Black MyoF samples compared to White MyoF samples but not in the Black F samples compared to White F samples.…”
Section: Resultsmentioning
confidence: 99%